Special Provisions for the Medicines Registration Procedure in Response to Economic Restrictions Imposed on the Russian Federation - E. M. Rychikhina (Регуляторные исследования и экспертиза лекарственных средств)
The economic sanctions imposed on the Russian Federation in 2022 create a potential risk of shortages or absence of a range of medicines demanded by the Russian healthcare system. The article describes the legislative measures by the Russian Government aimed at prevention of inventory shortages of medicinal products and, in particular, the special requirements to expert evaluation and registration of the medicines that could be affected by the risk. The article pays special attention to the time frames of assessment and registration procedures.